Depression and Sleep Issues in Aging: A Prospective Study: Depression and Sleep Issues in Aging - Umer, Ayesha; Jahangir, Saman; Gul, Mahnoor; Sohail, Tahoor (Pakistan Journal of Health Sciences, 2022)
Clinical research has demonstrated a strong link between sleep issues and depression. Objective: To evaluate depression and sleep issues in aging. Methods: A subset of the Alameda County (California) Study's questionnaires from 1994 and 1995 (N=2,370) had data on major depressive episode symptoms and sleep issues. The authors examined a number of variables, including ages, sex, education, relationship status, social isolation, functional disability, financial difficulties, and alcohol consumption. Twelve items covering the Diagnostic and Statistical Manual of Mental Disorders-IV as a criterion for severe, moments of depression i.e. sleeplessness and hypersomnia, were used to quantify depression. Results: In 1994, the prevalence of insomnia were 23.1% and hypersomnia were 6.7%. Depression was significantly predicted by sleep, gender, old age, social isolation, low education, financial instability, and physical handicap. Sleep issues and depression were evaluated prospectively with other variables controlled for, and depression in 1995 was predicted by sleep issues in 1994. Anhedonia, Thoughts of mortality, unworthiness, psychomotor agitation or impairment, mood fluctuation, and irritation were so much effective indicators of future severe depression. Conclusion: Future depression risk is highly correlated along with sleep problems and certain other severe depression-related symptoms. Sleep problems seem being little significant indicator of being depressive. Further epidemiological researches are required to determine proportional impact on various depressive indicator of developing major depressive disorder.